Approach to death and dying patients and its relation with death anxiety among medical interns: a multicenter cross-sectional study - Israa Sharabati; Mohamed M. M. Mustafa; Masah Ateeq; Hasan Al-jabali; Amira Ahmed Elsayed; Ahmed Hamdy Kandil; Mohamed Nabil Hamouda; Noor Alrawajfeh; Sadeel Abu Sharib; Razan A. Abumayyala; Omar Rafeek Alkhateeb; Mira Bishtawi; et al. (BMC Psychology)
Abstract Background Dealing with death and dying patients is one of the most challenging aspects of medical practice. The purpose of this study was to assess the attitude of medical interns toward death and dying patients as well as their level of death anxiety. Methods This cross-sectional study was conducted on medical interns across three countries—Egypt, Jordan, and Palestine—using an online survey created with Google Forms. The survey included sociodemographic information, the Approach to Death and Dying Patients Attitude Scale (ADDPAS), and Templer's Death Anxiety Scale (DAS). The sample size was calculated using OpenEpi, aiming for minimum 466 from Egypt, 273 from Jordan, and 348 from Palestine. Data were analyzed using SPSS version 27. Kruskal–Wallis and Mann–Whitney U tests were used to evaluate significant associations between demographic variables and the outcomes of the scales. Spearman’s correlation coefficients and simple linear regression analysis assessed the relationship between the scales. A p-value of ≤ 0.05 was considered statistically significant. Results This cross-sectional study analysis was done on 1156 participants. The median age was 24 years (interquartile range “IQR”: 24–25), with most living in urban areas (74.6%). Females comprised 53.6%. The median score on the DAS was 8.00 (IQR: 6–11). Hardness in communicating with the dying and their relatives and avoidance of death and dying patients subscales median scores were 2.22 (IQR: 1.89–2.44) and 2.54 (IQR: 2.18–2.81), respectively. Females had higher death anxiety and a less positive attitude toward communicating with dying patients and their relatives. Egypt scored lower on the ADDPAS subscales but higher than Palestine and Jordan on the DAS. DAS had a significant indirect relationship with hardness in communicating with the dying patients and their relatives (r = -.384; p < 0.001) and avoiding death and dying patients (r = -.123; p < 0.001). Simple linear regression showed that the DAS significantly predicts both subscales. Conclusions Medical interns showed moderate death anxiety and a positive attitude toward communication and avoidance of death and dying patients. Those with a higher level of death anxiety demonstrated a greater tendency to avoid dealing with dying patients and had more difficulties with communication. End-of-life training is recommended.